1992
DOI: 10.1038/ki.1992.431
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transvenous angioplasty in the treatment of vascular access stenosis

Abstract: This study was undertaken to evaluate percutaneous transvenous angioplasty (PTVA) for the treatment of all types of vascular access stenosis in a large population of dialysis patients. Stenoses were identified by venography in patients who met a set of clinical criteria indicating the need for evaluation. The lesions were classified by location and type. Data were collected prospectively and analyzed separately for each lesion type. A total of 536 PTVA procedures was performed in 285 patients. This included 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
245
3
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(263 citation statements)
references
References 26 publications
7
245
3
8
Order By: Relevance
“…1,[15][16][17][18][19][20][23][24][25][26][27][28] Additionally, also in common with other authors, 20,21 we did not observe superior patency in angioplasties with stents. Notwithstanding, our results differ with …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…1,[15][16][17][18][19][20][23][24][25][26][27][28] Additionally, also in common with other authors, 20,21 we did not observe superior patency in angioplasties with stents. Notwithstanding, our results differ with …”
Section: Discussionsupporting
confidence: 69%
“…Rates of immediate technical success of angioplasties conducted with a balloon alone can vary from 70 to 90%. 1,[15][16][17][18][19][20] In a study conducted by Kovalik et al, 16 in 1994, the authors observed that there were two types of central venous injuries: non-elastic lesions, which respond well to angioplasty, and elastic lesions, which do or do not respond to angioplasty. Therefore, elastic lesions tend to maintain less patency in relation to non-elastic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeding artery, arteriovenous anastomosis, draining vein(s) and central veins up to the right atrium were visualized. After identification of the stenoses, angioplasty was performed using a standard technique (10,11). …”
Section: Pretreatment Fistulography and Ptamentioning
confidence: 99%
“…Success rates are dismal (11,21,(52)(53)(54) because vessel injury to the endothelium and smooth muscle cells within the media that occurs after the PTA leads to further development of neointimal hyperplasia and restenosis (13,55). This suggests that although PTA may be important to treat stenosis in AVF and AVG, drug therapies may need to be applied to the site of angioplasty and endothelial injury to promote vascular healing and prolong vascular access patency.…”
Section: Endovascular Therapiesmentioning
confidence: 99%